Fissures of traditional culture in the novel Shadow Partisan by Nađa Tešić (Heritage, 2024)
The paper deals with representations of traditional culture and their deconstruction in Nađe Tešić's novel Shadow Partisan. The tangle of cultural symbolism, socio-historical dynamics and psychological dimensions shown in the novel is considered in an interdisciplinary key, through literary, cultural and ethnological-anthological readings.The goal of the research is to shed light on the influence of encoded patterns of traditional culture on the development of characters and the constitution of the story, as well as to look at the narrative processes that manifest the heroine's rebellion against traditional norms.The first part of the paper provides a theoretical framework for recognizing the so-called folk ideas, that is the world view that emerges from traditional cultural patterns and the effects on the world of the literary text. By the aspects of traditional culture in the novel we mean religious and spiritual practices, ritual-ordinary complexes, everyday rituals (such as culinary ones), folk medicine, oral folklore and legends, but also power relations and gender roles.With regard to the genre determination - bildungsroman, the given cultural framework is also examined as the backbone of the identity of the community and the individual who matures in it. We come to the conclusion that in the novel the fissures of traditional culture and through them identity, spirituality and all the value-normative creations of the world of the novel are revealed narratively.
Keywords: tradition; folklore; maiden novel; customs; rituals; magic; curse